PENGARUH PEMBERIAN PUPUKCAIR BIOGAS TERHADAP PERTUMBUHAN BIBIT KARET(Hevea brasiliensis) PADA STUM MINI KLON PB 260 - Arif Hidayat; Husna Yetti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
To determine the effect of biogas and liquid fertilizer to get a dose of where best to improve seedling performance. This study was conducted over three months, from May to July 2016. This study is an experiment using a completely randomized design (CRD) non factorial which consists of 5 treatments and 4 replications. The parameters of the observation that the increase of plant height, increase the number of leaves, increase the girth, leaf area, the ratio of the canopy and root dry weight of seedlings. The results showed liquid biogas fertilizer on seedling significant effect on the increase of plant height, leaf area and canopy ratio roots. To obtain good growth increase in seedling can be given a dose of 250 ml / plant. Keywords:liquid manure biogas, rubber seeds, clones PB 260